The criminal law as an instrument of the media to control society - Portillo Acosta, Rodrigo (2017)
What criminal legislation is doing throughout our region is to take an absolutely repressive tinge, with a total ineffectiveness against real problems; It simply sells illusions that through laws and aggravation of penalties the problems are solved, it naturally does not solve anything. They are witnessing a new idolatry, due to the inability of the political establishment to resolve conflicts, which do not care to solve them, but to sell the impression or feeling that they are solved, all this driven by  the mass media (Mediatic criminology), which construct the criminal issue through vindictive, repressive speeches, criminal stereotypes and systematic repetition of violent news, showing only social risks, homicides and common crimes, hiding other real dangers that threaten the population, causing Moral panic in society and the acceptance of police controls.